The foundations of female entrepreneurship : enterprise, home and household in London, c. 1800-1870 - Kay, Alison C. , 1973- (Routledge studies in business history, 2009)
Offers insights into the motivations of the Victorian women who opted to pursue enterprises of their own. This book argues that industrialization inaugurated a commercial and retail revolution that is responsible for the creation of niche markets and service industries, expanding the variety of opportunities for women.